Neural correlates of visuomotor adjustments during scaling of human finger movements. (July 2017) - Brand, Johannes; Michels, Lars; Bakker, Romy; Hepp‐Reymond, Marie‐Claude; Kiper, Daniel; Morari, Manfred; Eng, Kynan
Abstract: Visually guided finger movements include online feedback of current effector position to guide target approach. This visual feedback may be scaled or otherwise distorted by unpredictable perturbations. Although adjustments to visual feedback scaling have been studied before, the underlying brain activation differences between upscaling (visual feedback larger than real movement) and downscaling (feedback smaller than real movement) are currently unknown. Brain activation differences between upscaling and downscaling might be expected because within‐trial adjustments during upscaling require corrective backwards accelerations, whereas correcting for downscaling requires forward accelerations. In this behavioural and fMRI study we investigated adjustments during up‐ and downscaling in a target‐directed finger flexion–extension task with real‐time visual feedback. We found that subjects made longer and more complete within‐trial corrections for downscaling perturbations than for upscaling perturbations. The finger task activated primary motor (M1) and somatosensory (S1) areas, premotor and parietal regions, basal ganglia, and cerebellum. General scaling effects were seen in the right pre‐supplementary motor area, dorsal anterior cingulate cortex, inferior parietal lobule, and dorsolateral prefrontal cortex. Stronger activations for down‐ than for upscaling were observed in M1, supplementary motor area (SMA), S1 and anterior cingulate cortex. We argue that these activation differences may reflect differing online correction for upscaling vs. downscaling during finger flexion‐extension. Abstract : Scaling the visual feedback of finger movements elicited longer and more complete within‐trial corrections for downscaling perturbations than for upscaling perturbations. Accordingly, stronger fMRI activations for downscaling than for upscaling adjustments were found in sensorimotor brain regions. We conclude that sensorimotor brain regions (in particular S1) play an important role in online error correction.